Takradhara - A Procedure Review - Siddesha Ramappa Malakkanavar,; G. S. Hadimani,; Akshay R. Shetty, (International Journal of Ayurveda and Pharma Research, 2025)
Takradhara, a specialized form of Shirodhara in Ayurvedic medicine, involves the rhythmic application of medicated Takra over the forehead, facilitating both physical and mental healing. This therapy is particularly effective for psychosomatic and neurological conditions, benefiting those with ailments such as insomnia, diabetic neuropathy, psoriasis, hypertension, and various mental health disorders. While similar to Shirodhara, Takradhara’s distinction lies in its primary therapeutic agent, Takra, which has unique properties due to its cooling, Vata-Pitta balancing, and rejuvenating effects. The rich lactic acid content in Takra, combined with the therapeutic application, helps diminish stress, enhances cerebral circulation, improves memory, nourishes the scalp, and calms both mind and body. These benefits are achieved through Takradhara’s capacity to regulate Doshas, especially balancing Pitta and pacifying Vata, making it an effective intervention for a range of conditions from dermatological issues to neurological and metabolic disorders.